2020
DOI: 10.1016/j.culher.2020.06.008
|View full text |Cite
|
Sign up to set email alerts
|

An on-site Raman and pXRF study of Joseph Coteau and Philippe Parpette’s jewelled porcelain: a summit of ceramic art

Abstract: Highlights:-Non-invasive mobile approach to characterise artist materials implemented in Modern paintings -Validation of Specular Reflectance Infrared Spectroscopy analyses to identify paint binders -Combination of Raman and infrared spectroscopy for identifying Modern paints binders and pigments -Contactless spectroscopic identification of the binders and pigments of polymeric paints -On-site analytical study of artworks by German and Italian painters of the 1960s Abstract . Seven artworks representing the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 65 publications
0
26
0
Order By: Relevance
“…Pigments applied to English porcelain from a related period have previously been discussed. [ 24,49,50,72–74,76 ]…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Pigments applied to English porcelain from a related period have previously been discussed. [ 24,49,50,72–74,76 ]…”
Section: Discussionmentioning
confidence: 99%
“…The higher the lead oxide concentration, the higher the depolymerisation will be, lowering the melting point and hence the intensity of the 996 cm −1 band. Colomban et al [ 50 ] reported that lead‐rich enamels exhibit a strong stretching band at 980 cm −1 and alkali‐lead enamels which are less depolymerised and therefore have less flux, are fired at a higher temperature and are characterised by a band at ~1000–1010 cm −1 . And enamels with strong components at 1048 and 1050 cm −1 are characteristic of an alkaline‐rich glass.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations